Investigation of Radiation-induced Transcriptome Profile of Radioresistant Non-small Cell Lung Cancer A549 Cells Using RNA-seq - Yang, Hee Jung (Public Library of Science, 2013)
Radioresistance is a main impediment to effective radiotherapy for non-small cell lung cancer (NSCLC). Despite several experimental and clinical studies of resistance to radiation, the precise mechanism of radioresistance in NSCLC cells and tissues still remains unclear. This result could be explained by limitation of previous researches such as a partial understanding of the cellular radioresistance mechanism at a single molecule level. In this study, we aimed to investigate extensive radiation responses in radioresistant NSCLC cells and to identify radioresistance-associating factors. For the first time, using RNA-seq, a massive sequencing-based approach, we examined whole-transcriptome alteration in radioresistant NSCLC A549 cells under irradiation, and verified significant radiation-altered genes and their chromosome distribution patterns. Also, bioinformatic approaches (GO analysis and IPA) were performed to characterize the radiation responses in radioresistant A549 cells. We found that epithelial–mesenchymal transition (EMT), migration and inflammatory processes could be meaningfully related to regulation of radiation responses in radioresistant A549 cells. Based on the results of bioinformatic analysis for the radiation-induced transcriptome alteration, we selected seven significant radiation-altered genes (SESN2, FN1, TRAF4, CDKN1A, COX-2, DDB2 and FDXR) and then compared radiation effects in two types of NSCLC cells with different radiosensitivity (radioresistant A549 cells and radiosensitive NCI-H460 cells). Interestingly, under irradiation, COX-2 showed the most significant difference in mRNA and protein expression between A549 and NCI-H460 cells. IR-induced increase of COX-2 expression was appeared only in radioresistant A549 cells. Collectively, we suggest that COX-2 (also known as prostaglandin-endoperoxide synthase 2 (PTGS2)) could have possibility as a putative biomarker for radioresistance in NSCLC cells.